Air pollution in Bishkek, Kyrgyzstan: Driving factors and state response - Kenesh O. Dzushupov; Julian M. A. Buban; Arsen A. Aidaraliev; Attaullah Ahmadi; Priyanka Chahal; Muiz Ibrahim; Xu Lin; M. B. N. Kouwenhoven (Wiley, 2022)
Abstract The present article aims to describe the status quo of the atmospheric air quality in Bishkek and the state measures taken to improve it and to give the perspective of research and policy development. Air pollution is one of the major environmental risks for premature death from respiratory diseases, cancer, strokes, heart attacks, diabetes, and other diseases. It exerts a negative effect on worker productivity and mental health. In the last 30 years, Bishkek, the capital of the Kyrgyz Republic, has turned from one of the cleanest and greenest cities in the former Soviet Union to one of the most polluted cities in the world. The roots of that transformation lie in the negative socio‐economic changes taking place in the country, including the population doubling of Bishkek mainly due to internal migration, uncontrolled construction of houses without relevant infrastructure, worsening socio‐economic conditions, increased number of used vehicles, and low quality of gasoline. The main sources of air pollution in Bishkek are domestic heating and vehicle exhaust fumes. During the winter, air pollution is aggravated by frequent temperature inversion and air stagnation due to air trapping by high‐rise buildings. The state's approaches and measures to address this issue are reflected in its laws and policies. The city and national government have taken a range of strategic measures to transform Bishkek into a green city with a favourable environment. Recommendations on research and policy development are provided in this perspective.